ANTESEDEN CUSTOMER SATISFACTION DAN DAMPAKNYA PADA PURCHASE INTENTION - Jonathan Banjarnahor (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This research analyzed the effects of service quality and customer experience to customer satisfaction and its impact on purchase intention of costumer internet services in West Jakarta. This research used hypothesis testing as a research design. The primary data were obtained through questionnaire distributed to 180 respondents who should be users of internet services from Telkomsel, Telkomsel Grapari West Jakarta. Data was anlyzed by Structural Equation Method (SEM). The results showed there were positives service qualities and customer experience effects to customer satisfaction. There were positive customer satisfaction effects to purchase intention. There were positive effects of service quality and customer experience to purchase intention. Implications for managers are to increase purchase intention through fulfilled customer satisfaction led from good service quality and customer experience. For reasearch, it can be done in other service providers and by adding extra variables, such as coporate image and brand trust.